"Sometimes I feel like a pharmacist": identity and medication use among adolescents with juvenile arthritis. Issue 1 (December 2016) - McDonagh, J.; Shaw, K.; Prescott, J.; Smith, F.; Roberts, R.; Gray, N.
Abstract Background Taking medicines as intended is difficult for everybody, but young people going through adolescence have greater problems than adults and younger children. One of the most important things that happen during the teenage years is the development of individual identities, which might not remain constant during this time and can be affected deeply by the diagnosis of a long-term condition. The aim of this study was to examine the relationships between identity and medication use among young people with juvenile arthritis. Methods A prospective qualitative study was undertaken to collect private online 'blog' style data from young people (aged 11–19 years) with juvenile arthritis, and their parents, to examine their views about their condition, identity, medication and use of health services. Participants were identified from a large paediatric hospital in the UK. Results Young people (n  = 21) with a median age 14 years (range 11–17 years) posted a median (range) of 8 (1–36) blogs and parents (n  = 6) posted 4 (1–12) blogs. Young people gave a strong sense of both private and public identity that was intertwined with their arthritis and treatment. It was evident that young people's self-care was intrinsically linked to their attempts to maintain a sense of individually and socially constructed definitions of normality. The act of taking medication, and the consequences (positive or negative) of that act, had an impact both personally and socially. Conclusions Young people with juvenile arthritis reflect on their medication as a factor affecting their perception of themselves. Acknowledging the roles of both personal and social identity will be important in any strategies to support optimal medication use. This includes an understanding of the identity transformations that young people can experience and how decision-making may be affected by their attempts to retain pre-diagnosis identities and/or develop new social identities.